Molecular modelling of the Garlic compound with the beta-cyclodextrin at the best computer simulation - Mahjoub, Mabroukah; ahwedi, Aziza; Hosouna, Boubaker (Journal of natural sciences, life and applied sciences, 2019)
The study involved the integration of Alliin with β_cyclodecxtrin at a different energy levels and angles. A total of 176 computer samples were created using the Gaussian 03 and Hyperchem 08 programs for drawing, integrating, simulating and calculating the potential energy surface value, through which the lowest energy value of 25.563423661-) kcal) was found at the " ninth” level and internal angle 225o. From these results, we have obtained the best inclusion complex between Alliin and β-cyclodecxtrin which is considered very useful for the industrial application of drug.